Clinical profile and management options in patients of Ludwig’s angina: a 5 year prospective study - Tripathy, Smruti Milan; B., Harikumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The objective of the study was to study the etiology, clinical presentation, bacteriology and management options in 38 cases of Ludwig’s angina. Methods: 38 patients of Ludwig’s angina admitted in ENT Department of Saveetha Medical College, between March 2012 to April 2017, were included in the study. Various parameters like etiological agents, clinical features and management options were analysed. Results: Ludwig’s angina was found to be more prevalent between age group of 41 to 70 years with a mean age group of (60.3yrs). Males were found to be more commonly affected (71%) as compared to females (29%). Odontogenic infections still accounted for majority (81%) of causes with uncontrolled type 2 diabetes mellitus emerging as the main associated comorbidity. Patients mainly presented with symptoms like submental and submandibular swelling (100%), dysphagia (67%), odynophagia (55%), and stridor (42%). Almost all the patients required intravenous antibiotics, analgesics and steroids (100%) with (82%) requiring tooth extraction and (74%) requiring incision and drainage. Among the patients who presented with stridor (29%) underwent tracheostomy for airway management. The culture of the discharge obtained after incision and drainage found pseudomonas (71%), staphylococcus aureus (34%) and beta hemolytic streptococcus (42%) as common microbial agents. Conclusions: Ludwig’s angina is a serious and life threatening condition which can have fatal outcome if not treated aggressively, therefore a thorough understanding of the clinical presentation, common etiological factors, microbial agents and treatment methods is needed to manage these patients.